2006
DOI: 10.1002/jrs.1513
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of degenerate four‐wave mixing and cavity ringdown signal intensities of formaldehyde in a molecular beam

Abstract: A comparison of degenerate four-wave mixing (DFWM) and cavity ring-down (CRD) spectroscopy is made on jet-cooled formaldehyde under identical expansion conditions. We show that both methods are applicable to the low-density environment of a molecular beam. However, a slightly superior signalto-noise ratio for the background-free DFWM method is observed for our experimental configurations. Absorption spectra simulated by applying an asymmetric rotor model are used to deduce Boltzmann temperatures of the rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The low-wavenumber spectrum of liquid water has been investigated with four-photon coherent spectroscopy to interrogate the orientational motion of the H 2 O molecule. 148 Shimada et al 149 discovered a new molecular phenomenon in a resonance HR scattering study of liquid solutions. 145 Taking advantage of the coherent Raman emission from stimulated Raman generation, Echevarria et al 146 showed that increases in the chain length and the number of CH 3 groups in alcohols enhance the Raman emission efficiency.…”
Section: Other Nonlinear Techniquesmentioning
confidence: 99%
“…The low-wavenumber spectrum of liquid water has been investigated with four-photon coherent spectroscopy to interrogate the orientational motion of the H 2 O molecule. 148 Shimada et al 149 discovered a new molecular phenomenon in a resonance HR scattering study of liquid solutions. 145 Taking advantage of the coherent Raman emission from stimulated Raman generation, Echevarria et al 146 showed that increases in the chain length and the number of CH 3 groups in alcohols enhance the Raman emission efficiency.…”
Section: Other Nonlinear Techniquesmentioning
confidence: 99%
“…MgSO 4 was mixed with the paraformaldehyde to remove water from the formaldehyde vapor [25]. The formaldehyde vapor was entrained in a stream of Kr at a stagnation pressure of 1 bar.…”
Section: Methodsmentioning
confidence: 99%
“…However, the reduction of the DFWM signal intensities to population densities is not fully established, in particular for polyatomic molecules. A comparative study of DFWM with Cavity Ringdown (CRD) spectroscopy has been performed on jet-cooled formaldehyde by Tulej et al 21 Absorption spectra are simulated by applying an asymmetric rotor model and assuming a Boltzmann temperature for the rotational distribution in the molecular beam. A simple model for the reduction of the DFWM signal intensities to population is applied, yielding an absorption-like spectrum in accordance with both the simulations and the CRD measurements.…”
Section: New Developments In Non-linear Optical Spectroscopy 631mentioning
confidence: 99%